(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The poetics of exile has insuperable politics attached to it. The expatriate’s act of articulation whether intended or not is political in nature. Dislocation, cultural and geographical, forces the expatriate to take a fresh measure of his being and belonging. The desire to find a sustainable stand in the socio-political structure of the adopted homes is met with a rigorous resistance from the established structures and their politically unacknowledged nevertheless clearly visible hierarchies of discrimination. These structures by denying easy acceptability or conversely through an easy accommodation into the existing slots force the expatriate upon himherself. The situation induces a crisis whereby the expatriate has to look in and look out, look back and look at hisher existence vis-à-vis the predetermined constricting frames of identification to negotiate a sustainable sense of identity.